2021
DOI: 10.5603/arm.a2021.0012
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acute Exacerbation Following Bronchoalveolar Lavage in Patients with Suspected Idiopathic Pulmonary Fibrosis: A Retrospective Cohort Study

Abstract: Introduction: Bronchoalveolar lavage (BAL) is useful for diagnosing diffuse lung disease and excluding other conditions. However, acute exacerbations (AEs) are recognized as important complications of BAL in patients with idiopathic pulmonary fibrosis (IPF). This study aimed to identify risk factors for BAL-induced AEs in patients with IPF. Material and methods: We retrospectively analyzed the data of 155 patients with suspected IPF who had undergone BAL between January 2013 and December 2018. BAL-related AE w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Abe et al reported that the recovery rate of BALF in patients with AE of idiopathic pulmonary fibrosis after BAL was 17%–56%. 20 If the recovery rate is less than 50%, the frequency of complications may be higher. Our study demonstrated that use of the left bronchus during BAL and lower respiratory function led to a lower recovery rate of BALF in CFIP.…”
Section: Discussionmentioning
confidence: 99%
“…Abe et al reported that the recovery rate of BALF in patients with AE of idiopathic pulmonary fibrosis after BAL was 17%–56%. 20 If the recovery rate is less than 50%, the frequency of complications may be higher. Our study demonstrated that use of the left bronchus during BAL and lower respiratory function led to a lower recovery rate of BALF in CFIP.…”
Section: Discussionmentioning
confidence: 99%
“…The 30-day time frame allowed us to capture the two procedure-related fatalities, which occurred 20 and 29 days after the intervention and may have gone unnoticed with a shorter follow-up period ( Table 4 ). Furthermore, we attributed to the procedure not only the death caused by an adverse event (i.e., AE-IPF), which had already been associated with bronchoscopy [ 40 , 41 ], but also the death ultimately caused by septic shock. The latter patient ended up in the ICU due to a severe immediate adverse event of bronchoscopy (air embolism), and the subsequent complications (bilateral pneumonia, respiratory failure, and septic shock) that developed and ultimately caused his death would likely not have occurred if he had not undergone the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression analyses were used to investigate risk factors for the PF-ILD, and continuous variables were converted into dichotomous variables mainly through the median cut-off. The cut-off value was 70.0% for FVC% predicted and 50.0% for DLCO% predicted (Abe et al, 2021;Lacedonia et al, 2022). Survival curves were obtained using the Kaplan-Meier method, and Cox proportional analyses were performed to identify prognostic factors for mortality.…”
Section: Discussionmentioning
confidence: 99%